The Effect Of Compound Exercises on Strength and Speed of Neurotransmitters, Muscle Electrical Activity and Direct Free Kick Scoring Accuracy For Youth Footballers - Shakir, Habib; Jaber, Jasem; Hussein, Hossam (Journal of Physical Education, 2019)
The Effect Of Compound Exercises on Strength and Speed of Neurotransmitters, Muscle Electrical Activity and Direct Free Kick Scoring Accuracy For Youth FootballersThe importance of the study lies on identifying the effect of compound exercises on strength and speed of the neurotransmitters, electrical activity and direct free kick scoring accuracy in youth football. The researchers have used the experimental approach with two equivalent groups because of its practicality. The sample of the research was the footballers of the Al Diwaniyah Club, they were (20) players. They have been divided into two groups control and experimental, each group has (10) players.  Necessary tools and equipment have been used during the study. Preparing compound exercises, exploratory and field experiments have been carried out. Those procedures have included pre measurements, then the compound exercises have been carried out, they have concluded with post measurements. The researchers have concluded that the players are in need of such compound exercises to develop strength and speed of the neurotransmitters, electrical activity and scoring accuracy through a direct free kick for youth.